ANALISIS KINERJA KEUANGAN BANK GO PUBLIC DAN BANK NON GO PUBLIC DI INDONESIA - hilmi prasetio budi (Jurnal Ilmu Manajemen (JIMMU), 2020)
The purpose of this study is: to test whether or not there is a go public linkage with the financial performance of the bank and to determine whether there are differences in financial performance of bank go public and non-go public bank.The sample used in this research is a banking company go public and non-go public bank listed in the bank Indonesia and presents the financial statements of the period 2013 to 2015. The results of this study indicate that there is no link to go public with the financial performance of the bank. In addition, there is no difference between the performance of the bank go public with the performance of non-go public banks. In this research using camel minus management method with 4 variables.